The Role of Parents in Shaping the Character of the Alpha Generation of Elementary School Age in the Digital Era - Indriani, Fitri (Jurnal Indonesia Sosial Sains, 2024)
This research theoretically analyzes parents' role in shaping Generation Alpha's character at primary school age in the digital era. This research method uses qualitative methods of literature study. Research data sources are obtained from literature relevant to the research theme, such as books, scientific articles, or journals accessed from Google Scholar. Data analysis techniques use content analysis techniques. Furthermore, the results of the content analysis are concluded in accordance with the research objectives. The results showed that the role of parents in shaping the character of the alpha generation with the following details: (1) teach children to access various information through the internet correctly and be able to communicate civilly; (2) control or supervise the impressions accessed by the child; (3) limit the duration of time children play mobile phones; (4) invite children to play in open spaces to develop socially; (5) invite children to exercise or play that can develop children's physical motor. In addition to the five roles performed above, parents also need to fortify children with strong aqidah and ahklak and bring children closer to the Quran so that children's character is quickly developed and formed.